2003
DOI: 10.4049/jimmunol.170.8.4087
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Requirements for IL-7 in Development of TCRγδ Cells During Fetal and Adult Life

Abstract: TCRγδ-transgenic IL-7−/− mice were generated to determine whether T cells containing productively rearranged TCRγδ genes have additional requirements for IL-7 within the thymus or peripheral lymphoid tissues. Differences in developmental requirements for IL-7 by TCRγδ cells were noted and were linked to derivation from fetal- vs adult-type precursors in the thymus. Although TCRγδ cells are absent from IL-7−/− mice, TCRγδ cells were restored to the thymus and periphery by expression of TCRγδ transgenes. Endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 77 publications
4
22
0
Order By: Relevance
“…Likewise, ␥␦ T cell generation was rescued in IL-7 Ϫ/Ϫ mice upon grafting of an IL-7-expressing thymus (46). Additional BrdU labeling studies with ␥␦ TCR-transgenic IL-7 Ϫ/Ϫ mice suggested that IL-7, although not required for ␥␦ T cell survival, may increase the life span of proliferating cells, whereas other cytokines, such as IL-15, may be important for driving this proliferation (25), a prediction consistent with our present results. In regard to IL-15, studies indicated reductions in ␥␦ T cell subsets in IL-15 Ϫ/Ϫ , IL-15R␣ Ϫ/Ϫ , and IL-15R␤ Ϫ/Ϫ mice (26,47,48).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Likewise, ␥␦ T cell generation was rescued in IL-7 Ϫ/Ϫ mice upon grafting of an IL-7-expressing thymus (46). Additional BrdU labeling studies with ␥␦ TCR-transgenic IL-7 Ϫ/Ϫ mice suggested that IL-7, although not required for ␥␦ T cell survival, may increase the life span of proliferating cells, whereas other cytokines, such as IL-15, may be important for driving this proliferation (25), a prediction consistent with our present results. In regard to IL-15, studies indicated reductions in ␥␦ T cell subsets in IL-15 Ϫ/Ϫ , IL-15R␣ Ϫ/Ϫ , and IL-15R␤ Ϫ/Ϫ mice (26,47,48).…”
Section: Discussionsupporting
confidence: 82%
“…IL-7 signaling was shown to be absolutely required for the initiation of TCR␥ gene rearrangements (24). Consistent with this observation, ␥␦ T cells were absent in IL-7 Ϫ/Ϫ and IL-7R␣ Ϫ/Ϫ mice (22,23), but could be restored through introduction of a rearranged ␥␦ TCR transgene (25,45). Likewise, ␥␦ T cell generation was rescued in IL-7 Ϫ/Ϫ mice upon grafting of an IL-7-expressing thymus (46).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…4B). Thus, consistent with previous reports (38,39), our data also suggested that IL-7Ra-mediated signaling was responsible for both the initial expansion and maintenance of gd T cells.…”
Section: Il-7ra-mediated Signaling Is Required For Homeostasis Of Il-supporting
confidence: 81%
“…Both IL-7 and IL-15 have been implicated in ␥␦ T cell biology and might play a role in ␥␦ T cell homeostasis. IL-7 is essential for rearrangement of the TCR␥ gene during ␥␦ T cell development (22,23) and may also increase ␥␦ T cell life span in the periphery (24). Although IL-15 is not required for ␥␦ T cell development in general, IL-15 Ϫ/Ϫ mice lack V␥5 ϩ epidermal ␥␦ T cells (25) and Thy1 Ϫ splenic and intestinal intraepithelial ␥␦ T cells (16,26).…”
Section: Cd4 T Cells ͉ Cd8 T Cells ͉ Homeostatic Proliferationmentioning
confidence: 99%